Warm springs [videorecording (DVD)] - Sargent, Joseph, 1925-2014; Branagh, Kenneth; Nixon, Cynthia; Paymer, David; Bates, Kathy, 1948-; Nelson, Tim Blake; Alexander, Jane, 1939- (HBO Video, 2005)
The inspiring true story about Franklin Roosevelt, left a paraplegic from polio at 39 years of age, who seeks out a miracle cure in the backwoods of Georgia.